Peran Manajemen Keragaman Budaya dalam Kinerja Organisasi Non Profit Berbasis Aliansi (Studi Kasus pada Jakarta Centre for Law Enforcement Cooperation) - Ranita Agustina; Mahfudz Mahfudz (Diponegoro Journal of Economics, 2020)
Jakarta Centre for Law Enforcement Cooperation (JCLEC) is the cooperation jointly operates by the Government of Indonesia and the Australian Government. The problem in this study is how cultural diversity management can affect the performance of alliance-based nonprofit organizations. The purpose of this study is to analyze how the application of cultural diversity management consisting of awareness, internal dimensions, external dimensions, leadership, and policy, formed a conducive work environment to create competitive advantage for organizations and influence the organizational performance. The participants of this research were 8 people from Indonesia, Australia and Canada, with positions ranging from Directors to Managers. The diversity of the organizations is from Indonesian National Police (INP), Australian Federal Police (AFP), Royal Canadian Mounted Police (RCMP) combined with the civilian staff from Indonesia and Australia. This study used qualitative method with the case study approach. In-depth interviews, observation, and documentation were used as the research method. The results of the analysis show that the management of cultural diversity consisting of awareness, internal dimensions, external dimensions, leadership, and policies formed a conducive work environment. A conducive working environment where the cultural diversity is accepted and leading to the skill development of the staff is one of the key to create competitive advantage. The competitive advantage which created from the conducive working environment such as creativity and innovation is giving a lot of benefit for organizations and support organizational performance.